2020
DOI: 10.3892/mmr.2020.11184
|View full text |Cite
|
Sign up to set email alerts
|

miR‑199a‑3p suppresses cervical epithelial cell inflammation by inhibiting the HMGB1/TLR4/NF‑κB pathway in preterm birth

Abstract: Preterm birth (PTB) is the primary cause of neonatal mortality worldwide. Infection and inflammation are considered to be the primary causes of PTB. cervical remodeling is an important step in the process of preterm delivery, and the destruction of the cervical epithelial barrier and inflammation are important triggers of cervical remodeling. The aim of the present study was to determine the effect and underlying mechanism of microrna (mir)-199a-3p/high-mobility group box 1 protein (HMGB1) signaling in cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
1
13
1
Order By: Relevance
“…During labor, the IL1β level is increased due to the influx of leukocytes into intrauterine tissues, which can enhance the contractile potential of myometrial smooth muscle [24 ,25].In addition, it has been demonstrated that IL-1βcan increase prostaglandin production and MMP9 expression via NF-kappa B signaling pathway [26 ,27], which are known to induce cervical ripening and myometrial contractions[ 28 29]. There is higher expression of the subunit of NF-κB in membranes, cervix and myometrium [30,31]. NF-κB can be activated by pro-inflammatory cytokines such as TNF and IL1β, and microbial or viral components that activate toll-like receptors (TLRs) [32].…”
Section: Discussionmentioning
confidence: 99%
“…During labor, the IL1β level is increased due to the influx of leukocytes into intrauterine tissues, which can enhance the contractile potential of myometrial smooth muscle [24 ,25].In addition, it has been demonstrated that IL-1βcan increase prostaglandin production and MMP9 expression via NF-kappa B signaling pathway [26 ,27], which are known to induce cervical ripening and myometrial contractions[ 28 29]. There is higher expression of the subunit of NF-κB in membranes, cervix and myometrium [30,31]. NF-κB can be activated by pro-inflammatory cytokines such as TNF and IL1β, and microbial or viral components that activate toll-like receptors (TLRs) [32].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Most spontaneous preterm birth is caused by dominant or subclinical infection of the upper genital tract that results in a host anti-inflammatory response. 11 The destruction of the cervical epithelial barrier and an inflammatory response are important trigger factors for cervical remodelling, which is an important step in preterm delivery. 11 At present, transvaginal cervical tube length measurement is the best method to screen for the risk of premature delivery in pregnancy, but its application is limited, so it is necessary to find better screening indicators.…”
Section: Discussionmentioning
confidence: 99%
“…11 The destruction of the cervical epithelial barrier and an inflammatory response are important trigger factors for cervical remodelling, which is an important step in preterm delivery. 11 At present, transvaginal cervical tube length measurement is the best method to screen for the risk of premature delivery in pregnancy, but its application is limited, so it is necessary to find better screening indicators. 12 The differentially expressed proteins identified in this present study were mainly from the complement and coagulation cascade pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the qRT-PCR assay followed the methods of Peng et al with some modification [ 25 ]. Total RNA was extracted from H9c2 cells using TRIzol reagent (Invitrogen, USA) and then reverse transcribed using a PrimeScript RT reagent kit (Takara Biotechnology Co., Ltd.), following the manufacturer's instructions (with the temperature protocol of 37°C for 15 min and 85°C for 5 sec).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was used to examine the expression levels of proteins in this study; the method followed the methods of Peng et al with some modifications [ 25 ]. Each group of H9c2 cells was harvested and lysed in RIPA buffer with protease inhibitors (Invitrogen, USA), and the protein concentrations were determined by the Pierce BCA assay (Invitrogen, USA), according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%